Factor contributing to water shortage issue due to urbanisation in Pahang - Nurulhuda, Zakaria (2017)
Urbanisation of an area are complex and dynamic with many external and internal factors driving growth, movement, and composition. On of issue often related with urbanisation is water shortage. Water shortage is the lack of sufficient available water supply to meet water needs within a region. The main objective of study was to identify the factors contributing to water shortage issue due to urbanisation in Pahang. To achieve the main objective, study were performed to forecasting population growth and domestic water demand. Then, compare domestic water demand and water supply in 5 districts in Pahang. Secondary data which are number of population and volume of water supply obtained from local authority and by using statistical approach, the population projected and domestic demand trend derived as output. Analysis show that domestic demand increases along the population over the years. The unchanging volume of water supply by water treatment plant no longer can meet the demand of water users that increases due to rising development in urban area. Therefore, water shortage occurs in affected areas. The results of this study shows urbanisation give significance impacts to the water demand. Therefore to maintain continuous water supply without facing water shortage, the authorities could consider to include development growth and urbanisation in water planning.